SYSTEMATIC LITERATURE REVIEW: SPIRITUAL LEADERSHIP DALAM KONTEKS MANAJEMEN - Hanif Silmi Khomsin; Elisabeth Supriharyanti (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This research aims to examine the spiritual leadership model of leadership as popular research. Leadership is an important factor in an organization in influencing its followers to achieve certain goals. Spiritual leadership can theoretically shape behavior into three, namely vision, hope/faith and altruistic love. The method used was a systematic literature review (SLR) approach, by identifying 29 relevant articles taken from the Scopus database which were analyzed. The results of this research indicate that spiritual leadership aims to have a positive impact on the organization so that it requires development in testing spiritual leadership with technological advances.